Emerging Diabetic Novel Biomarkers of the 21st Century - Suneja, Shilpa; Gangopadhyay, Sukanya; Saini, Vandana; Dawar, Rajni; Kaur, Charanjeet (Annals of the National Academy of Medical Sciences (India), 2021)
Diabetes is a growing epidemic with estimated prevalence of infected to reach ~592 million by the year 2035. An effective way to approach is to detect the disease at a very early stage to reduce the complications and improve lifestyle management. Although several traditional biomarkers including glucated hemoglobin, glucated albumin, fructosamine, and 1,5-anhydroglucitol have helped in ease of diagnosis, there is lack of sensitivity and specificity and are inaccurate in certain clinical settings. Thus, search for new and effective biomarkers is a continuous process with an aim of accurate and timely diagnosis. Several novel biomarkers have surged in the present century that are helpful in timely detection of the disease condition. Although it is accepted that a single biomarker will have its inherent limitations, combining several markers will help to identify individuals at high risk of developing prediabetes and eventually its progression to frank diabetes. This review describes the novel biomarkers of the 21st century, both in type 1 and type 2 diabetes mellitus, and their present potential for assessing risk stratification due to insulin resistance that will pave the way for improved clinical outcome.
Keywords: 21st century; biomarkers; review; type 1 diabetes mellitus; type 2 diabetes mellitus